Staff Guidance Note for the Conduct of Ex Post Peer Reviewed Assessments of Members with Longer-Term Program Engagement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2016)
This note updates guidance on key operational aspects of the policy on Longer-Term Program Engagement (LTPE). The updated guidance reflects operational changes following the Board's decision on April 30, 2015 to replace Ex Post Assessments (EPAs) for members with LTPEs with succinct ex post peer reviewed assessments (PRAs)1 to reflect on the lessons from the past for the design of successor arrangements or usage of the Policy Support Instrument (PSI).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fund Arrangement; Longer-Term Program Engagement; PP; PRA Finding; PRA